Effects of the substitution of gallium with boron on the physical and mechanical properties of Ni-Mn-Ga shape memory alloys - Aydogdu, Yildirim; Turabi, Ali Sadi; Kok, Mediha; Aydogdu, Ayse; Tobe, Hirobumi; Karaca, Haluk Ersin (Springer Heidelberg, 2014)
The effects of the substitution of gallium with boron on the physical, mechanical and magnetic shape memory properties of Ni51Mn28.5Ga20.5-xBx (at.%) (x = 0, 1, 2, 3) polycrystalline alloys are investigated. It has been found that transformation temperatures are decreasing while hardness is increasing with boron addition. B-doping of NiMnGa alloys results in the formation of a second phase that increases its ductility and strength in compression. Moreover, saturation magnetization of austenite is decreasing, while Curie temperature of austenite is increasing with B-doping.
Keywords: Magnetic-Properties; Martensitic-Transformation; Phase; Fe; Microstructure; Transitions; Crystal